2016
DOI: 10.1186/s40687-015-0049-2
|View full text |Cite
|
Sign up to set email alerts
|

The Lerch Zeta function III. Polylogarithms and special values

Abstract: This paper studies algebraic and analytic structures associated with the Lerch zeta function, complex variables viewpoint taken in part II. The Lerch transcendent (s, z, c) := ∞ n=0 z n (n+c) s is obtained from the Lerch zeta function ζ (s, a, c) by the change of variable z = e 2πia . We show that it analytically continues to a maximal domain of holomorphy in three complex variables (s, z, c), as a multivalued function defined over the base manifold C × (P 1 (C) {0, 1, ∞}) × (C Z) and compute the monodromy fun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 69 publications
1
18
0
Order By: Relevance
“…It also bears the name of Lerch [19], who showed that for ℑz > 0 and q ∈ (0, 1) the functional equation ζ(z, q; 1 − s) = (2π) −s Γ(s) e( 1 4 s − zq)ζ(−q, z; s) + e(− 1 4 s + zq)ζ(q, 1 − z; s) holds; this is called Lerch's transformation formula. For an interesting account of the analytic properties of the Lipschitz-Lerch zeta function and related functions, we refer the reader to the work of Lagarius and Li [15][16][17][18]; see also Apostol [2].…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…It also bears the name of Lerch [19], who showed that for ℑz > 0 and q ∈ (0, 1) the functional equation ζ(z, q; 1 − s) = (2π) −s Γ(s) e( 1 4 s − zq)ζ(−q, z; s) + e(− 1 4 s + zq)ζ(q, 1 − z; s) holds; this is called Lerch's transformation formula. For an interesting account of the analytic properties of the Lipschitz-Lerch zeta function and related functions, we refer the reader to the work of Lagarius and Li [15][16][17][18]; see also Apostol [2].…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…In both cases, the meromorphic extension is continuous on its domain of holomorphy as a function in the two variables (s, w). We refer to [26] for much deeper knowledge on the meromorphic continuability of the Lerch transcendent as a function of all three variables. It suffices to show that for a, b ∈ A and p ∈ P a,b the map Recall that (without loss of generality) E a and E b are subsets of C. For M ∈ N 0 , let…”
Section: 7mentioning
confidence: 99%
“…This property was noted in Parts II and III ( [29,30]). When restricting to real variables, we regard ∂ ∂a and ∂ ∂c as real differential operators.…”
Section: Introductionmentioning
confidence: 59%
“…The Hurwitz zeta function inherits the discontinuities of the Lerch zeta function at integer values of c. Milnor [32, p. 281] noted that at the value s = 1 the space K s includes on (0, 1) the odd function c − [29,30]) for which the Lerch zeta function is an eigenfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation